Acute Toxicity (LC50 96 Hours) of Organophosphate Pesticide With Poksim Active Compound And Haematology And Histopathology Review Goldfish (Cyprinus carpio L) - Dewi Nur Setyorini; Diana Arfiati; Asus Maizar Suryanto Hertika (Indonesian Journal of Environment and Sustainable Development, 2015)
This research has the objectives to determine LC50 96 hours value and observation toward hematology, gills and kidney histology of goldfish (Cyprinus carpio) exposed to organophosphate pesticide with Poksim active compound (trade brand FOKKER 500 EC). Method used in this paper is experiment to determine LC50 96 hour value with probit analysis. Descriptive method was used for gills and kidney tissues microanatomy observation with hematoxilin eosin (HE) coloring and hematology. Toxicity result of Fokker 500 EC pesticide toward goldfish obtained LC50 96 hours with 41,7 ppm. Histological result showed that increasing exposure doses in real test had caused increase gills and kidney tissues damage. Hematology observation result during research obtained that along with the increasing exposure doses of pesticide in the real test, acute toxicity test would caused reduction in total erythrocyte, leukocyte and hemoglobin of goldfish. Result also showed that Fokker pesticide usage was allowed until 1,8 ppm dose based on histology and hematology evaluation. Keywords: acute toxicity, goldfish, histology, hematology, pesticide